The Cultural Meaning in Verbal and Non Verbal Expression Represented in Nyaébuh Tradition of People in Aeng Tong-tong, Saronggi, Sumenep - Hodairiyah, Hodairiyah; Rais, Wakit Abdullah; Purnanto, Dwi (Bina Nusantara University, 2019)
This research aimed to find out the cultural meaning of verbal and non-verbal expression represented in the nyaébuh tradition of people in Aeng tong-tong, Saronggi, Sumenep. This research was a qualitative descriptive using an ethnographic method with ethnoscience analysis. Data were obtained from the interview result with two informants of verbal and non-verbal expression. It finds that this tradition in the form of almsgiving whereby the charity is devoted to the deceased in the hope that it can alleviate and erase the sins of the deceased, in addition to which it can increase unity, harmony, family, harmony between people and others. This research can provide the benefits of knowledge about the meaning contained in the tradition of nyaébuh, and it can give the Sumenep community’s insights about the meaning of tradition through verbal and non-verbal language expressions. Besides that, it can share knowledge about the culture and traditions of Madura for each different region.